Implementing DAGUSIBU to Enhance Pediatric Medication Management at Posyandu Aster: Penerapan DAGUSIBU sebagai Upaya Meningkatkan Pengelolaan Obat Anak di Posyandu Aster - Rima Haerunnisa; Annisa Nismaul Husna; Dewi Rahmawati (B-Creta Publisher, 2026)
Safe and responsible medication management is crucial to prevent medication errors in the community. The DAGUSIBU (Obtaining, Using, Storing, and Disposing of Medication) program aims to raise public awareness about proper medication management. This activity was implemented at the Aster Integrated Health Post (Posyandu) using an interactive educational approach through counseling and leaflet distribution to 30 participants. Participants' knowledge was assessed using pre-test and post-test questionnaires. Results showed a significant increase in the average knowledge score, from 16.17 to 19.47 after the intervention. This increase was evenly distributed across all age groups. These findings demonstrate the effectiveness of DAGUSIBU outreach in increasing public knowledge about pediatric medication management, thereby supporting safer medication use and reducing the risk of medication errors. This activity has the potential to become a model for ongoing education in public health programs